Power performance : multimedia storytelling for journalism and public relations - Silvia, Tony.; Anzur, Terry (Malden, MA : Wiley-Blackwell, 2011)
"With television news anchors becoming daily celebrity guests in our homes and traditional news media turning increasingly to multimedia enhancements, there is a growing need for journalists and public relations practitioners to develop essential presentation skills. This is the first book available for professionals and students interested primarily in transmitting news and information on-camera in multi-media formats, rather than working behind the scenes. Writing, reporting, and producing skills are examined specifically in terms of their application to effective communication with the viewing audience of both traditional and new media. A guide to storytelling skills for journalism and public relations in multiple media platforms, including print, broadcast, and the web, this book offers invaluable behind-the-scenes insights and profiles of leading multimedia journalists and public relations practitioners. Practical advice is offered on how to put presentation skills to work and the key ethical issues are addressed. This book will appeal to working professionals seeking to enhance their skills, students, citizen journalists and anyone interested in breaking in to on-camera journalism and public relations."--
Foreword / by Lester Holt -- Introduction -- The Role of the Storyteller -- Reporting Stories Across Media -- Writing the Story for Print and the Web -- Video Storytelling on the Air and on the Web -- Presenting the Story On-Camera, On-Air, and On-line -- Practicing Public Relations in a Multimedia World -- Ethical Journalism in Multicultural Media -- Putting Your Skills to Work.
Includes bibliographical references.
Keywords: Mass media -- Authorship; Broadcast journalism; Reporters and reporting; Public relations -- Authorship; Journalism; Social Science; SOCIAL SCIENCE -- Media Studies; LANGUAGE ARTS & DISCIPLINES -- Journalism; Broadcast journalism; Mass media -- Authorship; Public relations -- Authorship; Reporters and reporting; Journalistiek; Multimedia; Presentatie; Berichtgeving; Electronic books